Development of technology for biological treatment of oily wastewater with а consortium of microorganisms, microalgae and aquatic plants - Yernazarova, G.I.; Bukharbayeva, Zh.M.; Zayadan, B.K.; Turasheva, S.K.; Omarova, G.K. (KU Publ., 2021)
The article describes the diversity of oil products that are the main sources of wastewater pollution. The dissolved or liquefied oil forms a floating layer on the water surface. The large emissions of different crude oil sources and household waste into the environment cause great damage to wildlife. It is evident that many types of oil sources are carcinogens. The article provides information on emissions of toxic compounds of industrial enterprises into the atmosphere and their adverse effects, including on human health because toxic compounds can cause many diseases. The methods of biotechnological treatment by mechanical, physicochemical and biological purification of water sources contaminated with oil waste are discussed. In particular, the importance of biological purification, petroleum technology, and microbiological purification and nanotechnological methods of water purification has been widely examined. The article contains information on water purification method using microalgae, biological filters, and wastewater treatment through aerotanks. Methods to purify phenolic compounds from wastewater such as adsorption, ion exchange, liquid-liquid extraction, chemical oxidation, electrochemical methods, solvent extraction, precipitation and biodegradation are considered. The role of some economically efficient and promising methods of bioremediation to eliminate and neutralize petroleum hydrocarbons and some pollutants in removing phenolic compounds is analysed.
Мұнаймен ластанған ағынды суларды микроорганизмдер, микробалдырлар және су өсімдіктерінің консорциумынан биологиялық тазарту технологиясын жасау
Разработка технологии биологической очистки нефтесодержащих сточных вод c помощью консорциума микроорганизмов, микроводорослей и водных растений
Keywords: biological purification; microorganisms; microalgae; pollution; environment; biotechnology; phenol